Wärmewende in der multiplen Krise – die Rolle der Gasindustrie und die Kämpfe um eine sozial-ökologische Transformation der Wärmeversorgung - H. Sander (Geographica Helvetica, 2024)
The article examines the current German heat transition as a central conflict about socio-ecological transformation. It analyzes the struggles on the decarbonization of the mainly fossil-based heat production and supply on different scales perceiving them as conflicts about the hegemonic regulation of society-nature-relations. Using a historical materialist policy-analysis as an operationalization of marxist political ecology and state theory the author discusses the neoliberalization of nature and the multiple crisis as a context in which four hegemony projects emerged. The actors of these projects that are based in a specific political economy try to achieve their long-term strategies in the current political disputes on how to decarbonize the heat supply in German cities. These debates are further examined on the municipal scale taking the case of Berlin as an example. The analysis shows that those processes crystallize in the question whether the corporate gas-based infrastructure will be adjusted by means of green gases resp. hydrogen or whether it will be transformed to a new system based on renewable energies resp. heatpumps.